2018
DOI: 10.1039/c7ra13524f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of triblock copolymer polydopamine-polyacrylic-polyoxyethylene with excellent performance as a binder for silicon anode lithium-ion batteries

Abstract: Triblock copolymer polydopamine-polyacrylic-polyoxyethylene with strong adhesion as a novel binder enhance the cycle performance of silicon anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…In the case of a Si‐based system, the cyclic stability also strongly depends on the binders, since an effective binder can prevent the Si particles from pulverization and subsequently electrical isolation . If this isolation occurs, the peak width and position in the HAXPES Si 1s spectra is affected by the charge‐up effect arising from the continuous photoelectron emission under high electron‐beam density .…”
Section: Applications Of Advanced Characterization Methods To Siliconmentioning
confidence: 99%
“…In the case of a Si‐based system, the cyclic stability also strongly depends on the binders, since an effective binder can prevent the Si particles from pulverization and subsequently electrical isolation . If this isolation occurs, the peak width and position in the HAXPES Si 1s spectra is affected by the charge‐up effect arising from the continuous photoelectron emission under high electron‐beam density .…”
Section: Applications Of Advanced Characterization Methods To Siliconmentioning
confidence: 99%
“…在以上的三种粘结剂中, PAA 的研究最热, 除上述 以外, 研究人员还利用 PAA 合成聚丙烯酸-脲基-嘧啶酮 (PAA-UPy) [80] 、 聚 多 巴 胺 -聚丙烯酸 -聚氧乙烯 (PDA-PAA-PEO) [81] 、聚丙烯酸-聚(乙二醇-共-苯并咪 唑)(PAA-PEG-PBI) [82] 等交联粘结剂, 都取得不错的结 果.…”
Section: C-cmc-ca 交联粘结剂unclassified
“…However, their insulating nature in electronic and ionic conduction still impedes the high-power performance of the electrodes, although some progress was achieved by modifying the polysaccharide matrices through blending and graing them with electroactive oligomers or small molecular groups. [14][15][16][17] The blending of polysaccharide-based binders with a polymer containing ionically conductive groups provides a substantial enhancement of lithium ion transport in the electrode, and thus improves the cycling behavior of Si-based anodes. Recent works have demonstrated that the lithium ion conduction in polymeric binder is signicantly improved with the addition of polyethylene glycol (PEG) to polysaccharide and other polymeric binders, leading to enhanced electrochemical performance of Si-based anodes.…”
Section: Introductionmentioning
confidence: 99%
“…PEG-based block or gra copolymers have also been examined as high performance binders for Si anodes. 15,16,19 For example, triblock linear copolymer polydopamine-polyacrylic-polyoxyethylene binder has been shown to improve the cycle performance and reversible capacity for silicon anodes compared to Si/PVDF electrode due to its strong adhesion and high ion conductivity. 15 Some studies on graing high adhesive polymer to polysaccharide binder have also shown enhanced electrochemical performance of Si anodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation